Gross Private Capital Flows to Emerging Markets : Can the Global Financial Cycle Be Tamed? - Nier, Erlend (IMF Working Papers; Working Paper ;, 2014)
This paper assesses empirically the key drivers of private capital flows to a large sample of emerging market economies in the last decade. It analyzes the effect of the global financial cycle, measured by the VIX, on capital flows and investigates the role of fundamentals and country characteristics in mitigating or amplifying its effect. Using interaction models, we find the effect of the VIX to be non-linear. For low levels of the VIX, capital flows are driven by fundamental factors. During periods of stress, the VIX becomes the dominant driver of capital flows while other determinants, with the exception of interest rate differentials, lose statistical significance. Our results also suggest that the effect of global financial conditions on gross private capital flows increases with the host country's level of financial sector development. Finally, our results imply that countries cannot fully insulate themselves from global financial shocks, unless creating a fragmented global financial system.